Dialogism in historical measurements of the old Ukrainian time - Peredriienko, Vitalii (Ukrainian linguistics, 2017)
The book review: Dialogism in historical measurements of the old Ukrainian time: Otrys Kliryka Ostrozkogo / Prepar. of the scientific research, text, pointers by O. I. Nikа. Kyiv: Education of Ukraine, 2016. 238 pp. Information about the author: Vitalii Peredriienko – PhD, Associate Prof. of the Department of General and Slavic Linguistics, National University of “Kyiv-Mohyla Academy” (Ukraine). https://scholar.google.com.ua/citations?user=yCzAS9oAAAAJ&hl